2005
DOI: 10.1016/j.febslet.2005.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ABC transporter ABCB1 expressed in human neural stem/progenitor cells

Abstract: We investigated the localization and functional expression of the ABC transporter ABCB1 in human fetal neural stem/progenitor cells (hNSPCs). RT-PCR analysis revealed ABCB1 gene expression in hNSPCs. We found a single band in immunoblotted hNSPCs lysates probed with ABCB1 antibody, and detected ABCB1 at the hNSPCs cell membrane by immunocytochemistry and subcellular fractionation. ABCB1 inhibitors and substrate, and ATP-depleting agents enhanced hNSPCsÕ rhodamine 123 accumulation, and hNSPCs microsomes had van… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 35 publications
2
42
1
Order By: Relevance
“…Further study revealed that cultured hNSPCs expressed functional ABCB1 as well as ABCG2 at the cell surface, and that their expression was downregulated during differentiation of hNSPCs, similar to the downregulation of ABCG2 in HSCs at the stage of lineage commitment [143,167,168]. It was observed that both ABC transporters were downregulated during hNSPC differentiation, together with nestin downregulation and GFAP upregulation (Figures 2 Cell Research | www.cell-research.com ABC transporters and neurogenesis 864 npg and 3).…”
Section: Abc Transporters and Nscsmentioning
confidence: 80%
See 4 more Smart Citations
“…Further study revealed that cultured hNSPCs expressed functional ABCB1 as well as ABCG2 at the cell surface, and that their expression was downregulated during differentiation of hNSPCs, similar to the downregulation of ABCG2 in HSCs at the stage of lineage commitment [143,167,168]. It was observed that both ABC transporters were downregulated during hNSPC differentiation, together with nestin downregulation and GFAP upregulation (Figures 2 Cell Research | www.cell-research.com ABC transporters and neurogenesis 864 npg and 3).…”
Section: Abc Transporters and Nscsmentioning
confidence: 80%
“…It was found that more than half of the hNSPCs within neurospheres expressed nestin, an NSPC marker [167,168]. Furthermore, all nestin+ cells simultaneously expressed ABCB1 [167,168].…”
Section: Abc Transporters and Nscsmentioning
confidence: 99%
See 3 more Smart Citations